Effect of Torulaspora delbrueckii and Saccharomyces cerevisiae fermentation on chemical composition of ciders made from traditional Finnish apple cultivars - Wang, Qizai; Laaksonen, Oskar; Jafari, Mahsa Sadat; Okwum, Ada Obianuju; Damerau, Annelie; Heinonen, Maarit; He, Wenjia; Yang, Baoru; Kelanne, Niina (Elsevier, 2026)
This study investigated the impact of two yeast strains, Saccharomyces cerevisiae (SC) and Torulaspora delbrueckii (TD), on the chemical composition of ciders prepared from the juices of six traditional apple cultivars grown in Finland, aiming to evaluate the potential of these underutilized local cultivars for cider production. Sugars, organic acids and ethanol contents were analyzed using gas chromatography coupled with a flame ionization detector (GC–FID), while volatile compounds were identified and semi-quantified using headspace solid-phase microextraction coupled with gas chromatography–mass spectrometry (HS–SPME–CG–MS). Apple cultivar selection had a stronger impact than yeast strain on the sugars and organic acids in ciders, whereas both factors shaped the volatile compound profiles. Among the cultivars, ‘Rambo’ demonstrated the greatest potential for cider aroma development. Specifically, fermentation of ‘Rambo’ juice with TD yielded the highest ester production among all TD-fermented ciders. Volatile profiling further revealed that TD favored the formation of fruity esters while reducing higher alcohol and acetic acid levels, resulting in potentially more complex and fruity aroma, compared to SC. Other cultivar–yeast combinations, such as ‘Aleksanteri’, ‘Antonovka’, or ‘Mustialan Iso Venäläinen’ with SC, could also enhance cider aroma complexity. These findings highlight the potential of underutilized apple cultivars, when combined with tailored yeast selection, to diversify cider profiles and to enhance sensory quality.
Keywords: Traditional cultivar; Finland; yeast; non-Saccharomyces; cider; volatiles